2012
DOI: 10.1093/icvts/ivs203
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and operative repair of Morgagni hernia

Abstract: We conclude that preoperative diagnosis and early diagnosis of MH by using laparotomy and thoracotomy is useful for safe and effective repair. Also we suggest that resection of the hernia sac and insertion of a mesh are not necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 10 publications
2
54
1
4
Order By: Relevance
“…Ligament laxity is an essential and constant factor to arise a GV (13,16). Some others predisposing factors are mentioned such as gastric repletion, repeated vomiting and factors that increase the abdominal pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Ligament laxity is an essential and constant factor to arise a GV (13,16). Some others predisposing factors are mentioned such as gastric repletion, repeated vomiting and factors that increase the abdominal pressure.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that mesh repair for MH could be performed via laparotomy, thoracotomy and thoracoabdominal approach, but mesh insertion was not always necessary for diaphragmatic hernia (3,4). On the contrary, a retrospective review indicated that MH recurrence was high after laparoscopic repair in patients without patch, and more frequent use of patch may be beneficial (5).…”
Section: Discussionmentioning
confidence: 99%
“…[4] It usually presents with severe pulmonary symptoms in the early neonatal period; however, it is rarely symptomatic in adults and is usually incidentally diagnosed. [5] Nevertheless, adult patients with MH can show symptoms such as dyspnea, cough, chest pain, constipation,and gastric or intestinal obstruction symptoms and any delay in diagnosis may lead to devastating results. [5][6][7] Regardless of the fact that the patient is either symptomatic or asymptomatic, MH requires a surgical treatment due to risks of obstruction or strangulation.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Nevertheless, adult patients with MH can show symptoms such as dyspnea, cough, chest pain, constipation,and gastric or intestinal obstruction symptoms and any delay in diagnosis may lead to devastating results. [5][6][7] Regardless of the fact that the patient is either symptomatic or asymptomatic, MH requires a surgical treatment due to risks of obstruction or strangulation. [5] The surgical approach can be transthoracic which is usually suggested as the operative strategy in patients with previous abdominal operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation